THE EFFECT OF CRITICAL ELECTRIC FIELDS ON THE ELECTRONIC DISTRIBUTION OF BILAYER ARMCHAIR GRAPHENE NANORIBBONS - Lam Thuy Duong Nguyen; Thi Kim Quyen Nguyen; Nguyen Huu Hanh Pham; Dang Khoa Le; Van Chinh Ngo; Thi Kim Loan Phan; Anh Huy Huynh; Thanh Tra Vu (Tạp chí Khoa học Đại học Đà Lạt)
We employed tight-binding calculations and Green’s function formalism to investigate the effect of applied electric fields on the energy band and electronic properties of bilayer armchair graphene nanoribbons (BL-AGNRs). The results show that the perpendicular electric field has a strong impact on modifying and controlling the bandgap of BL-AGNRs. At the critical values of this electric field, distortions of energy dispersion in subbands and the formation of new electronic excitation channels occur strongly. These originate from low-lying energies near the Fermi level and move away from the zero-point with the increment of the electric field. Phase transitions and structural changes clearly happen in these materials. The influence of the parallel electric field is less important in changing the gap size, resulting in the absence of the critical voltage over a very wide range [–1.5 V; 1.5 V] for the semiconductor-insulator group. Nevertheless, it is interesting to note the powerful role of the parallel electric field in modifying the energy band and electronic distribution at each energy level. These results contribute to an overall picture of the physics model and electronic structure of BL-AGNRs under stimuli, which can be a pathway to real applications in the future, particularly for electronic devices.